2008
DOI: 10.4161/pri.2.3.7437
|View full text |Cite
|
Sign up to set email alerts
|

Biological and biochemical characterization of L-type-like bovine spongiform encephalopathy (BSE) detected in Japanese black beef cattle

Abstract: A case of L-type-like atypical bovine spongiform encephalopathy was detected in 14-year-old Japanese black beef cattle (BSE/ JP24). To clarify the biological and biochemical properties of the prion in BSE/JP24, we performed a transmission study with wildtype mice and bovinized transgenic mice (TgBoPrP). The BSE/ JP24 prion was transmitted to TgBoPrP mice with the incubation period of 199.7 ± 3.4 days, which was shorter than that of classical BSE (C-BSE) (223.5 ± 13.5 days). Further, C-BSE was transmitted to wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
51
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 30 publications
4
51
0
Order By: Relevance
“…It is very difficult to precisely estimate the influences of age on atypical and classical BSE cases. Atypical BSE and classical BSE display unique incubation periods, PrP res deposition patterns, and histological lesions [9,16]. However, because the onset of BSE is affected by exposure dose of BSE agent and host susceptibility, it is difficult to estimate the infection time for both classical and atypical BSE cases.…”
Section: Discussionmentioning
confidence: 99%
“…It is very difficult to precisely estimate the influences of age on atypical and classical BSE cases. Atypical BSE and classical BSE display unique incubation periods, PrP res deposition patterns, and histological lesions [9,16]. However, because the onset of BSE is affected by exposure dose of BSE agent and host susceptibility, it is difficult to estimate the infection time for both classical and atypical BSE cases.…”
Section: Discussionmentioning
confidence: 99%
“…18 Lesion profile analysis revealed that the degree of brain vacuolation due to the Japanese L-type BSE isolate was similar to that caused by the other L-type BSE isolates (Fig. 1A).…”
Section: Acknowledgmentsmentioning
confidence: 70%
“…The analyses of L-type BSE cases have been performed using different bovinized PrP-overexpressing transgenic mice, such as TgBoPrP, 18 Tgbov XV 11,21 and Tg540. 22 Thus, it has been impossible to compare the properties of L-type BSE isolates in detail.…”
mentioning
confidence: 99%
“…Atypical BSEs are classified into 2 forms on the basis of the molecular weight of the proteinase K-resistant core fragment of the abnormal prion protein PrP Sc : L-type BSE (L-BSE) or bovine amyloidotic spongiform encephalopathy and H-type BSE (H-BSE) [3,5]. Several studies have indicated that L-BSE and H-BSE are caused by different prions with varying biological characteristics [4,11,12]. A limited number of atypical BSE cases have been reported, and sporadic occurrence may be supposed as their origin [2].…”
mentioning
confidence: 99%
“…Thereafter, this case was referred as L-BSE [9]. Cattle [6] and mice overexpressing bovine PrP [12] that had been experimentally challenged with L-BSE had a shorter incubation period and exhibited more severe spongiform changes in the brain than the mice and cattle that had been experimentally challenged with C-BSE. These results suggest that the L-BSE prion exhibits greater virulence in cattle than the C-BSE prion.…”
mentioning
confidence: 99%